Peningkatan Prestasi Belajar Siswa MTs Al Mubarok Bandar Mataram Lampung Tengah - Arianto Arianto (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
Behavior change is one that can be seen is student achievement is the result or level of ability that has been achieved by students after following the teaching and learning process in a certain time either in the form of behavioral changes, skills and knowledge and then will be measured and assessed which then manifested in the numbers or statements.The learning process and its results can only be observed from changes in different behaviors that were previously in a person in terms of knowledge, affective and psychomotor. Broadly speaking, the learning process is influenced by duafaktor, namely internal factors and external factors. Internal factors include physiological factors, ie student body and psychological factors, ie students' intelligence or intelligence, motivation, interests, attitudes, talents. External factors include the natural environment and the socio-cultural environment, while the non-social or instrumental environment, ie the curriculum, the program, the learning facilities, the teacher.